1997
DOI: 10.1007/bf02550928
|View full text |Cite
|
Sign up to set email alerts
|

Benign polyps with prostatic-type epithelium of the urethra and the urinary bladder

Abstract: The clinico-pathological features of nine urethral and urinary bladder polyps with prostate-type epithelium are described. The average age of the patients was 46 years. Three patients previously had cystoscopy and the lesion was not noticed on the initial examination. The commonest presentation in this series was haematuria, dysuria and frequency of micturition. One patient presented with postmicturition dribble and another with haemospermia. The polyps contained acini and papillae lined by prostate-type epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Based on the size and location of the lesion, this disease may present a variety of clinical symptoms. From a review of 22 other case reports (Table 1), the most common site of prostatic-type polyps in the bladder was the trigone and the most frequent presenting symptoms were haematuria and dysuria 627 Interestingly, in several cases, the condition was asymptomatic. Radiologic imaging and cystoscopy were commonly used to detect the disease and the lesion usually presented as an isoechoic mass on ultrasound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the size and location of the lesion, this disease may present a variety of clinical symptoms. From a review of 22 other case reports (Table 1), the most common site of prostatic-type polyps in the bladder was the trigone and the most frequent presenting symptoms were haematuria and dysuria 627 Interestingly, in several cases, the condition was asymptomatic. Radiologic imaging and cystoscopy were commonly used to detect the disease and the lesion usually presented as an isoechoic mass on ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…Prostatic-type epithelial polyps are unusual, benign lesions found in the urinary tract system. 1 The lesions were first described approximately 100 years ago 2 and are known by several synonyms including aberrant prostatic tissue, adenomatous polyps, benign villous polyps of the urethra and papillary adenoma of prostatic urethra. 3 Most commonly, the polyps grow on the posterior urethra and are seldomly found in the bladder.…”
Section: Introductionmentioning
confidence: 99%
“…It must be differentiated from the hypertrophied verumontanum. There are reports of a 1.5% recurrence rate after management with transurethral resection and an extremely rare potential for malignant transformation [1,3,4] .…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of diagnostic method used, transurethral resection and pathologic examination is required to confi rm diagnosis in order to exclude more malignant neoplasms such as urothelial papilloma (1,7,8,12). Multiple studies have shown that recurrence and severe complications after transurethral excision of FEP are infrequent (1,10,(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%